A transition metal catalyst and preparation method thereof

By using a support supported transition metal catalyst formed by cyclic P4O12 connection, the existing catalysts have been solved, and the high-efficiency hydrogen evolution performance in the entire pH range is achieved, exceeding the performance of commercial platinum carbon.

CN115679370BActive Publication Date: 2025-03-25JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211459644.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-03-25
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

The existing catalysts have low catalytic activity, relatively poor stability and cannot effectively evolve hydrogen reactions within the full pH range.

Method used

A carrier formed by a ring P4O12 connected to the MO6 polyhedron through M-O-P is loaded with a transition metal N to form a high-stability catalyst. The support has good conductivity and stability, and the activity of the catalyst under different pH environments is enhanced by phosphate groups.

Benefits of technology

The stability of the catalyst is significantly improved, so that its stability in acidic, alkaline and neutral solutions can reach thousands of hours, and the hydrogen evolution activity in the full pH range exceeds commercial platinum carbon and reaches the international leading level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115679370B_ABST
    Figure CN115679370B_ABST
Patent Text Reader

Abstract

The present invention provides a metaphosphate-loaded transition metal catalyst and a preparation method, which belong to the field of electrocatalytic water decomposition. The catalyst first prepares a transition metal hydroxide array, and the transition metal hydroxide array is used to prepare a transition metal metaphosphate array carrier by chemical vapor deposition. Then, the transition metal metaphosphate array carrier and the transition metal salt solution are used as working electrodes and electrolytes respectively by electrodeposition technology to prepare single-atom type, cluster type and particle type metaphosphate-loaded transition metal catalysts. The prepared metaphosphate-loaded transition metal catalyst is applied to an electrolytic cell in a full pH range and has excellent electrocatalytic hydrogen evolution performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrocatalytic water decomposition to produce hydrogen, and in particular to a transition metal catalyst and a preparation method thereof. Background Art

[0002] Excessive consumption of fossil fuels has led to global warming and environmental pollution. Hydrogen, as a green energy source, is regarded as an ideal alternative to fossil fuels. From the perspective of hydrogen production methods, water electrolysis is not only a safe and environmentally friendly way to produce hydrogen, but can also be combined with renewable energy sources such as solar and wind energy to improve energy efficiency. To date, platinum-based materials still have the best hydrogen evolution performance in solutions of all pH values. However, the high price and easy poisoning of platinum-based materials hinder their large-scale commercial application. An ideal hydrogen evolution electrocatalyst should have the characteristics of low cost, high stability, and can work effectively in a wide pH range. The challenge of developing pH-universal electrocatalysts stems from the fact that the hydrogen evolution reaction has different reaction mechanisms in different chemical environments. In acidic media, the material has a high affinity for protons (H3O + ) adsorption capacity determines the rate of hydrogen evolution reaction. In neutral and alkaline media, protons are provided by water molecules, so the electrocatalyst is required to have good water molecule adsorption and dissociation capabilities in the rate-limiting step of the reaction - the Volmer step. In order to obtain electrocatalysts with hydrogen evolution performance exceeding that of platinum-based materials in all pH ranges, intrinsic thermodynamic properties and structure-activity relationships should be considered. This work is extremely challenging but of great significance.

[0003] Supported metal catalysts, which fix metals on supports, play a key role in various nanotechnology applications, in which both supports and metals are very important. As active centers, changes in metal size (from single atoms, clusters to nanoparticles) usually affect surface electronegativity, energy, and interfacial reactivity. At the same time, supports are usually not inert and can regulate the spatial distribution, charge transfer, interface perimeter, and metal morphology of the metal through metal-support interactions. Specifically, orbital hybridization and charge transfer between supports and metals adjust the d-band center of the metal and enhance the adsorption capacity of reaction intermediates, thereby reducing the energy barrier and accelerating the rate-determining step. Carbon materials, carbon nitrides, sulfides, and nitrides can all be used as supports for metals. However, most of them cannot achieve hydrogen evolution activity beyond Pt-C and long-term stability due to interface instability such as metal particle agglomeration and sensitivity to pH changes. Summary of the invention

[0004] The purpose of the present invention is to provide a transition metal catalyst to solve the technical problems of low catalytic activity, relatively poor stability and inability to effectively perform hydrogen evolution reaction in the full pH range of existing catalysts. 12The transition metal N is loaded on a carrier formed by connecting MOP and MO6 polyhedrons, which greatly improves the stability of the transition metal catalyst.

[0005] Specifically, the present invention adopts a cyclic P4O 12 The carrier formed by connecting MOP and MO6 polyhedrons contains PO4 with infinite shared angles. 3- Tetrahedral chains, also containing PO4 with limited sharing of 3, 4, 6 and 12 corners 3- Ring. The unique chain structure makes it have good conductivity. And metal oxide (MO)-phosphate (PO4) 3- The presence of M in the unit also ensures the stability of the carrier itself. Furthermore, the phosphate group can not only act as a proton acceptor, but also induces a distorted local metal geometry that is conducive to the adsorption of water molecules, both of which are conducive to the hydrogen evolution reaction. 3- The group can play a protective role to prevent the solution from corroding the catalyst during the reaction, and can also firmly anchor the metal material attached to the surface to prevent the metal from dissolving or aggregating, thereby improving the stability of the material.

[0006] According to the above description, the present invention is characterized in that the cyclic P4O 12 The carrier formed by connecting MOP and MO6 polyhedrons includes metaphosphate, but is not limited thereto. The transition metal N is selected from iron, cobalt, nickel, platinum, ruthenium, iridium, and palladium; the transition metal M is selected from iron, cobalt, and nickel. The transition metal N can be in any form, including but not limited to transition metal single atoms, transition metal clusters, or transition metal particles.

[0007] In order to ensure a larger contact area with the solution and reduce the amount of metal used, the size of the transition metal N is less than 10 nm.

[0008] In certain preferred embodiments, the carrier has a rich microstructure to increase the specific surface area; for example, a rod array structure, with transition metals loaded on the rod surface.

[0009] Using metaphosphate as a carrier, the high stability catalyst of the present invention is obtained by the following steps:

[0010] Step 1: preparing a transition metal M hydroxide array;

[0011] Step 2: preparing a metaphosphate array of transition metal M by chemical vapor deposition of the transition metal hydroxide array prepared in step 1;

[0012] Step 3: using the transition metal metaphosphate array and metal N salt solution obtained in step 2 as the working electrode and electrolyte, respectively, to prepare metal metaphosphate-supported metal single atoms, clusters and particle array catalysts by electrodeposition technology;

[0013] According to the present invention, a transition metal hydroxide array is first prepared. The preparation method of the transition metal hydroxide array is not particularly limited and can be prepared by a hydrothermal method, a solvent thermal method, a chemical vapor deposition method, a chemical deposition method or an electrodeposition method well known to those skilled in the art, preferably a hydrothermal method or an electrodeposition method.

[0014] The hydrothermal method preferably dissolves the metal salt solution of M in a solvent in a reactor and fully dissolves it, then washes the conductive substrate with dilute hydrochloric acid, ethanol, and deionized water and obliquely inserts it into the reactor; after sealing the reactor, put it into a blast oven and react at 100-200°C for 5 hours, preferably at 110°C, and after natural cooling, repeatedly rinse with ethanol and deionized water to obtain a transition metal hydroxide array. The metal salt in the metal salt solution of M is preferably one of the nitrates and chlorides of iron, cobalt or nickel, more preferably cobalt nitrate, nickel nitrate, ferrous sulfate, or nickel sulfate; the solvent is preferably urea and ammonium fluoride; the conductive substrate is preferably carbon cloth, carbon paper, nickel mesh, copper mesh, titanium mesh or titanium sheet.

[0015] According to the present invention, the transition metal hydroxide array prepared above is used to prepare a transition metal metaphosphate array by chemical vapor deposition; specifically preferably, the obtained transition metal hydroxide array is placed in a magnetic boat, the non-metallic powder is placed in another magnetic boat, the two magnetic boats are placed in a tube furnace and reacted at 250-600°C for 1-3 hours, preferably at 300-500°C, and the transition metal metaphosphate array is obtained after cooling. The non-metallic powder is preferably sodium hypophosphite, and 1.5g of non-metallic powder is used for each 2cm×4cm transition metal hydroxide array.

[0016] According to the present invention, the transition metal metaphosphate array obtained above is used as a working electrode, a graphite sheet is used as a counter electrode, and silver / silver chloride is used as a reference electrode in a three-electrode system using a CHI760E electrochemical workstation for electrodeposition, the electrolyte is a metal salt solution of N, the electrodeposition temperature is preferably 25-35°C, the number of electrodeposition cycles is 2-30 cycles, more preferably 5-15, and most preferably 15 cycles, the electrodeposition method is preferably cyclic voltammetry, the voltage is preferably -0.2-1.4 volts, and the deposited sample is washed with deionized water and ethanol to obtain a metal metaphosphate-supported metal single atom, cluster and particle array catalyst. The metal salt in the metal salt solution of N is preferably cobalt chloride, nickel nitrate, cobalt sulfate, ferrous sulfate, nickel sulfate, chloroplatinic acid, ruthenium chloride, iridium chloride and palladium chloride.

[0017] The present invention also provides the use of the metal single atom, cluster and particle array catalyst supported by the metal metaphosphate in an electrolytic cell with a full pH range. The metal single atom, cluster and particle array supported by the metal metaphosphate is used as a cathode, and its electrocatalytic hydrogen evolution performance in an electrolyte with a full pH range is tested using a CHI760E electrochemical workstation.

[0018] Beneficial effects of the present invention:

[0019] The present invention is based on cyclic P4O 12 The carrier-loaded metal catalyst formed by connecting MOP and MO6 polyhedrons greatly improves the stability of the catalyst. Its stability in acidic, alkaline and neutral solutions can reach thousands of hours. Its activity can surpass commercial platinum carbon in the entire pH range, reaching the international leading level. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope photograph of the metal nickel hydroxide nanosheet array prepared in Example 1;

[0021] Figure 2 The infrared spectra of the metal nickel metaphosphate array catalyst prepared in Example 1 and the nickel metaphosphate-supported ruthenium single atom catalyst prepared in Example 2 and the corresponding unit cell schematic diagrams;

[0022] Figure 3 The nickel metaphosphate array catalyst prepared in Example 1;

[0023] Figure 4 This is a spherical aberration electron microscope photo of the nickel metaphosphate-supported ruthenium single-atom catalyst prepared in Example 2;

[0024] Figure 5 This is a spherical aberration electron microscope photo of the nickel metaphosphate-supported ruthenium cluster catalyst prepared in Example 3;

[0025] Figure 6 This is a spherical aberration electron microscope photo of the nickel metaphosphate-supported ruthenium particle catalyst prepared in Example 4;

[0026] Figure 7 The hydrogen evolution polarization curves of the nickel metaphosphate array catalyst prepared in Example 1 and the metal metaphosphate-supported ruthenium single atom, cluster and particle array catalysts obtained in Examples 3, 4 and 5 under acidic conditions; wherein s represents a single atom, c represents a cluster, and n represents a particle;

[0027] Figure 8 This is a hydrogen evolution polarization curve of the nickel metaphosphate supported ruthenium particle catalyst prepared in Example 5 under neutral conditions;

[0028] Fig. 9 This is a hydrogen evolution polarization curve of the nickel metaphosphate supported ruthenium particle catalyst prepared in Example 5 under alkaline conditions;

[0029] Fig.10 Synchrotron radiation data graphs of the metal nickel metaphosphate array catalyst prepared in Example 1, the nickel metaphosphate-loaded ruthenium single atom catalyst prepared in Example 2, the nickel metaphosphate-loaded ruthenium cluster catalyst prepared in Example 3, and the nickel metaphosphate-loaded ruthenium particle catalyst prepared in Example 4. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below with reference to the examples, and the raw materials involved in the examples are all commercially available.

[0031] Example 1 Preparation of nickel metaphosphate array catalyst

[0032] Step 1: Preparation of transition metal nickel hydroxide array

[0033] Dissolve 1.2 mmol of nickel nitrate, 6 mmol of urea and 2.4 mmol of ammonium fluoride in 30 ml of deionized water and stir for 20 minutes to mix the solution evenly. Next, transfer the solution to a 50 ml reactor. Wash the carbon cloth with dilute hydrochloric acid, ethanol and deionized water, take a 2 cm × 4 cm piece and insert it obliquely into the reactor and seal it. Place it in a forced air oven and react at 110 ° C for 5 hours. After cooling naturally, rinse and dry it repeatedly with ethanol and deionized water to obtain a nickel hydroxide nanosheet array. Figure 1 These are scanning electron microscope photographs of the prepared metal nickel hydroxide nanosheet arrays, where Figure a is a scanning electron microscope photograph at a 10-micron scale, and Figure b is a scanning electron microscope photograph at a 2-micron scale, which shows that the carbon cloth is completely covered by the extremely thin nickel hydroxide nanosheet arrays.

[0034] Step 2: Preparation of nickel metaphosphate array catalyst

[0035] Place the nickel hydroxide nanosheet array obtained in step 1 into a porcelain boat, place 1.5 grams of sodium hypophosphite powder into another porcelain boat, and then place the two magnetic boats into a quartz tube, wherein the magnetic boat containing the nickel hydroxide nanosheet array is placed in the high temperature zone, and the magnetic boat containing the sodium hypophosphite powder is placed in the low temperature zone, heat at 350°C for 2 hours under argon protection, and obtain a metal nickel metaphosphate array catalyst after cooling to room temperature.

[0036] By infrared spectroscopy ( Figure 2 a), the nickel metaphosphate array catalyst prepared in Example 1 has the following characteristics: Figure 2 The unit cell model shown in b shows that the metal nickel metaphosphate array catalyst is composed of cyclic P4O 12The structure is formed by connecting MOP and MO6 polyhedrons. Figure 3 It is a metal nickel metaphosphate array catalyst, where Figure a is a scanning electron microscope photo at a 5-micron scale, and Figure b is a scanning electron microscope photo at a 1-micron scale. The results show that during the high-temperature phosphating process, the originally flaky nickel hydroxide nanosheets are converted into a nickel metaphosphate array with a three-dimensional framework structure.

[0037] Example 2 Preparation of nickel metaphosphate supported ruthenium single atom catalyst

[0038] Step 1: preparing a transition metal nickel hydroxide array;

[0039] This step is the same as step 1 in Example 1.

[0040] Step 2: preparing a metal nickel metaphosphate array catalyst;

[0041] This step is the same as step 2 in Example 1.

[0042] Step 3: preparing a ruthenium single atom catalyst supported on nickel metaphosphate;

[0043] Electrodeposition was performed in a three-electrode system using the nickel metaphosphate array catalyst obtained in step 2 as the working electrode, a graphite sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte was 1 mM ruthenium chloride and 0.1 M sulfuric acid solution. In the Cyclic Voltammetry mode of the CHI760E electrochemical workstation, 5 cycles were deposited at 30°C with a potential range of -0.5 to 0.4 volts relative to the saturated calomel electrode. The sample after electrodeposition was washed with ethanol and water to obtain a ruthenium single atom catalyst supported on nickel metaphosphate.

[0044] Figure 4 The spherical aberration electron microscopy photos of the nickel metaphosphate-supported ruthenium single-atom catalyst prepared in Example 2, wherein Figure a is a spherical aberration electron microscopy photo at a scale of 5 nanometers, and Figure b is a spherical aberration electron microscopy photo at a scale of 2 nanometers. The bright spots in the figures are ruthenium atoms distributed in a single-atom state. According to synchrotron radiation data ( Fig.10 ) It can be confirmed that ruthenium atoms are loaded on the surface of the rod-shaped nickel metaphosphate.

[0045] Example 3 Preparation of nickel metaphosphate supported ruthenium cluster catalyst

[0046] Step 1: preparing a transition metal nickel hydroxide array;

[0047] This step is the same as step 1 in Example 1.

[0048] Step 2: preparing a metal nickel metaphosphate array catalyst;

[0049] This step is the same as step 2 in Example 1.

[0050] Step 3: preparing a ruthenium cluster catalyst supported on nickel metaphosphate;

[0051] Electrodeposition was performed in a three-electrode system with the nickel metaphosphate array catalyst obtained in step 2 as the working electrode, the graphite sheet as the counter electrode, and the saturated calomel electrode as the reference electrode. The electrolyte was 1 mM ruthenium chloride and 0.1 M sulfuric acid solution. In the Cyclic Voltammetry mode of the CHI760E electrochemical workstation, 10 cycles were deposited at 30°C with a potential range of -0.5 to 0.4 volts relative to the saturated calomel electrode. The sample after electrodeposition was washed with ethanol and water to obtain a nickel metaphosphate-loaded ruthenium cluster catalyst.

[0052] Figure 5 The spherical aberration electron microscopy photos of the ruthenium cluster catalyst supported by nickel metaphosphate prepared in Example 3, wherein Figure a is a spherical aberration electron microscopy photo at a scale of 5 nanometers, and Figure b is a spherical aberration electron microscopy photo at a scale of 2 nanometers. It can be seen from the figure that ruthenium atoms are aggregated into clusters with a particle size of about 1 nanometer, but there is no obvious lattice structure, no crystal phase, and it is a cluster of ruthenium. According to the synchrotron radiation data, it can be determined that the ruthenium clusters are supported on the surface of the rod-shaped nickel metaphosphate.

[0053] Example 4 Preparation of nickel metaphosphate supported ruthenium particle catalyst

[0054] Step 1: preparing a transition metal nickel hydroxide array;

[0055] This step is the same as step 1 in Example 1.

[0056] Step 2: preparing a metal nickel metaphosphate array catalyst;

[0057] This step is the same as step 2 in Example 1.

[0058] Step 3: preparing a ruthenium cluster catalyst supported on nickel metaphosphate;

[0059] Electrodeposition was performed in a three-electrode system using the nickel metaphosphate array catalyst obtained in step 2 as the working electrode, a graphite sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte was 1 mM ruthenium chloride and 0.1 M sulfuric acid solution. In the Cyclic Voltammetry mode of the CHI760E electrochemical workstation, 15 cycles were deposited at 30°C with a potential range of -0.5 to 0.4 volts relative to the saturated calomel electrode. The sample after electrodeposition was washed with ethanol and water to obtain a nickel metaphosphate-loaded ruthenium particle catalyst.

[0060] Figure 6The spherical aberration electron microscope photo of the ruthenium particle catalyst supported by nickel metaphosphate prepared in Example 4, wherein Figure a is a spherical aberration electron microscope photo at a scale of 5 nanometers, and Figure b is a spherical aberration electron microscope photo at a scale of 2 nanometers. It can be seen from the figure that the particle size of the ruthenium particles is about 2 nanometers, and there is a clear lattice structure, indicating that the ruthenium particles are very crystalline. The lattice spacing of 0.22 nanometers in Figure b corresponds to the 111 face of ruthenium metal. According to the synchrotron radiation data, it can be determined that the ruthenium particles are loaded on the surface of the rod-shaped nickel metaphosphate.

[0061] Example 5 Preparation of Cobalt Metaphosphate Supported Platinum Single Atom Catalyst

[0062] Step 1: preparing a transition metal cobalt hydroxide array;

[0063] This step is the same as step 1 in Example 1, the only difference being that 1.2 mmol of nickel nitrate is replaced by cobalt nitrate.

[0064] Step 2: preparing a metal cobalt metaphosphate array catalyst;

[0065] This step is the same as step 2 in Example 1.

[0066] The prepared metal cobalt metaphosphate array catalyst has the same Figure 1 The unit cell model shown in b shows that the metal cobalt metaphosphate array catalyst is composed of cyclic P4O 12 The structure is formed by connecting MOP and MO6 polyhedrons.

[0067] Step 3: preparing a platinum single atom catalyst supported by cobalt metaphosphate;

[0068] The metal cobalt metaphosphate array catalyst obtained in step 2 was used as the working electrode, the graphite sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode for electrodeposition in a three-electrode system. The electrolyte was 1 mM chloroplatinic acid and 0.1 M sulfuric acid solution. In the Cyclic Voltammetry mode of the CHI760E electrochemical workstation, 5 cycles were deposited at 30°C with a potential range of -0.5 to 0.4 volts relative to the saturated calomel electrode. The sample after electrodeposition was washed with ethanol and water to obtain a cobalt metaphosphate-supported platinum single atom catalyst.

[0069] Characterization: It can be seen from the spherical aberration electron microscope photograph that platinum is distributed in a single atomic state. According to the synchrotron radiation data, it can be determined that the platinum single atom is loaded on the surface of the rod-shaped cobalt metaphosphate.

[0070] Example 6 Preparation of iridium single atom catalyst supported by iron metaphosphate

[0071] Step 1: preparing a transition metal iron hydroxide array;

[0072] This step is the same as step 1 in Example 1, the only difference being that 1.2 mmol of nickel nitrate is replaced by iron nitrate.

[0073] Step 2: preparing a metal iron metaphosphate array catalyst;

[0074] This step is the same as step 2 in Example 1.

[0075] The prepared metal iron metaphosphate array catalyst has the same Figure 1 The unit cell model shown in b shows that the metal iron metaphosphate array catalyst is composed of cyclic P4O 12 The structure is formed by connecting MOP and MO6 polyhedrons.

[0076] Step 3: preparing an iridium single atom catalyst supported by iron metaphosphate;

[0077] The metal iron metaphosphate array catalyst obtained in step 2 was used as the working electrode, the graphite sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode for electrodeposition in a three-electrode system. The electrolyte was 1 mM chloroiridic acid and 0.1 M sulfuric acid solution. In the Cyclic Voltammetry mode of the CHI760E electrochemical workstation, 5 cycles were deposited at 30°C with a potential range of -0.5 to 0.4 volts relative to the saturated calomel electrode. The sample after electrodeposition was washed with ethanol and water to obtain the iridium single atom catalyst supported on the iron metaphosphate.

[0078] Characterization: According to the spherical aberration electron microscopy photograph, it can be seen that iridium is distributed in a single atomic state. According to the synchrotron radiation data, it can be determined that the iridium single atom is loaded on the surface of the rod-shaped iron metaphosphate.

[0079] Performance Characterization

[0080] (1) Testing the hydrogen evolution performance of the catalyst in an acidic solution (pH = 0)

[0081] The hydrogen evolution performance was tested in a three-electrode system with the catalysts obtained in Examples 2 to 6 as cathodes, graphite sheets as counter electrodes, and saturated calomel electrodes as reference electrodes. The electrolyte was a 0.5 M sulfuric acid solution. The hydrogen evolution process of the material was tested in the Linear Sweep Voltammetry mode of a CHI760E electrochemical workstation.

[0082] It can be determined through hydrogen evolution polarization curve analysis that the catalysts prepared in Examples 2 to 6 of the present invention all exhibit excellent hydrogen evolution performance under acidic conditions. Figure 7The hydrogen evolution polarization curves of the nickel metaphosphate-supported ruthenium single atom, cluster and particle array catalysts under acidic conditions are shown in Examples 2 to 4. Compared with the control samples of carbon cloth and nickel metaphosphate, the nickel metaphosphate-supported ruthenium single atom, cluster and particle array catalysts have a certain degree of performance improvement, among which the nickel metaphosphate-supported ruthenium particles have the best hydrogen evolution performance, and only 23.3 millivolts of overpotential are required to reach a current density of 10 milliamperes per square centimeter, which is even better than the catalytic performance of commercial platinum carbon (an overpotential of 25.0 millivolts is required to reach a current density of 10 milliamperes per square centimeter). This shows that the nickel metaphosphate-supported ruthenium particles have the potential to replace commercial platinum carbon.

[0083] (2) Testing the hydrogen evolution performance of the catalyst in a neutral solution (pH = 7)

[0084] The catalysts obtained in Examples 2 to 6 were used as cathodes, graphite sheets were used as counter electrodes, and saturated calomel electrodes were used as reference electrodes in a three-electrode system to test hydrogen evolution performance. The electrolyte was a 1M phosphate buffered saline solution. The hydrogen evolution process of the material was tested in the Linear Sweep Voltammetry mode of a CHI760E electrochemical workstation.

[0085] It can be determined through hydrogen evolution polarization curve analysis that the catalysts prepared in Examples 2 to 6 of the present invention all exhibit excellent hydrogen evolution performance under neutral conditions. Figure 8 The hydrogen evolution polarization curves of the nickel metaphosphate-supported ruthenium particle array catalyst obtained in Example 4 and the existing catalyst under neutral conditions are shown, wherein the nickel metaphosphate-supported ruthenium particles have the best hydrogen evolution performance, and only 35.4 millivolts of overpotential are required to reach a current density of 10 milliamperes per square centimeter, which is better than the catalytic performance of commercial platinum carbon (an overpotential of 43.2 millivolts is required to reach a current density of 10 milliamperes per square centimeter). This shows that the nickel metaphosphate-supported ruthenium particles still have good hydrogen evolution performance under acidic conditions.

[0086] (3) Testing the hydrogen evolution performance of the catalyst in alkaline solution (pH = 14)

[0087] The hydrogen evolution performance was tested in a three-electrode system with the catalysts obtained in Examples 2 to 6 as cathodes, graphite sheets as counter electrodes, and saturated calomel electrodes as reference electrodes. The electrolyte was a 1M potassium hydroxide solution. The hydrogen evolution process of the material was tested in the Linear Sweep Voltammetry mode of a CHI760E electrochemical workstation.

[0088] It can be determined through hydrogen evolution polarization curve analysis that the catalysts prepared in Examples 2 to 6 of the present invention all exhibit excellent hydrogen evolution performance under alkaline conditions. Fig. 9The hydrogen evolution polarization curves of the nickel metaphosphate-supported ruthenium particle array catalyst obtained in Example 4 and the existing catalyst under alkaline conditions are shown, wherein the nickel metaphosphate-supported ruthenium particles have the best hydrogen evolution performance, and only 35.9 millivolts of overpotential are required to reach a current density of 10 milliamperes / square centimeter, which is also better than the catalytic performance of commercial platinum carbon (an overpotential of 40.3 millivolts is required to reach a current density of 10 milliamperes / square centimeter). This shows that the nickel metaphosphate-supported ruthenium particles still have hydrogen evolution performance that exceeds commercial platinum carbon under alkaline conditions.

[0089] The embodiments of the present invention disclose a novel nickel metaphosphate-supported ruthenium single atom, cluster and particle array catalyst and a preparation method thereof.

[0090] Experimental results show that by controlling experimental parameters and changing experimental conditions, the hydrogen evolution performance of the new nickel metaphosphate-supported ruthenium single atom, cluster and particle array catalysts described in the present invention can surpass the performance of commercial platinum carbon.

Claims

1. A transition metal catalyst, characterized in that The invention comprises a transition metal N and a carrier for supporting the transition metal N, wherein the carrier is composed of a cyclic P4O 12 It is formed by connecting MOP and MO6 polyhedrons; the size of the transition metal N is less than 10nm; wherein M is a transition metal; the transition metal N is deposited on the carrier by electrodeposition; The carrier is prepared by the following method: Step 1: preparing a transition metal M hydroxide, and the prepared product is a transition metal M hydroxide array; The preparation method of the transition metal M hydroxide array is as follows: fully dissolving the transition metal M salt in a reaction kettle, and then obliquely inserting the conductive substrate into the reaction kettle; reacting at 100-200° C. for 5 hours; and washing after natural cooling to obtain the transition metal M hydroxide array; Step 2: Prepare transition metal metaphosphate by chemical vapor deposition of the transition metal M hydroxide prepared in step 1.

2. The catalyst according to claim 1, characterized in that The carrier has a rod array structure; the transition metal is loaded on the rod surface.

3. The catalyst according to claim 1, characterized in that The transition metal N is selected from iron, cobalt, nickel, platinum, ruthenium, iridium or palladium; the transition metal M is selected from iron, cobalt and nickel.

4. The catalyst according to claim 1, characterized in that The transition metal N is a transition metal single atom, a transition metal cluster or a transition metal particle.

5. The catalyst according to claim 1, characterized in that The conductive substrate is carbon cloth, carbon paper, nickel mesh, copper mesh, titanium mesh or titanium sheet.

6. The catalyst according to claim 1, characterized in that The transition metal M salt is selected from cobalt nitrate, nickel nitrate, ferrous sulfate, or nickel sulfate.

7. The catalyst according to claim 1, characterized in that The step 2 is specifically as follows: placing the transition metal M hydroxide array and the hypophosphite in two magnetic boats respectively, placing the two magnetic boats in a tube furnace and reacting at 250-600° C. for 1-3 hours; and taking out after cooling to obtain the metaphosphate array.

8. The catalyst according to claim 1, characterized in that The electrodeposition temperature is 25-35°C.

Citation Information

Patent Citations

  • Nickel metaphosphate micro-nanomaterial as well as preparation method and application thereof

    CN106185859A

  • Preparation method of monatomic platinum-loaded transition metal phosphide hydrogen evolution catalyst

    CN114807996A